Morphology and germination of the candlenut seed (Aleurites moluccana) from Samosir Island-North Sumatra. Issue 1 (February 2020) - Susilowati, A; Dalimunthe, A; Rachmat, H H; Elfiati, D; Sinambela, P Y; Ginting, I M; Larengkeng, S H
Abstract: Aleurites moluccana or locally known as kemiri or candlenut is domesticated multipurpose tree species found in Indonesia, particularly in North Sumatra. As one of high economic value commodities, candlenut can be adopted as agroforestry species, windbreak, soil immobilization and land rehabilitation for critical land that can improve community livelihood with a variety of benefits. Information regarding seed characteristics of the candlenut in North Sumatra Province and its germination strategies is still limited, whereas this information are needed to support candlenut cultivation. Therefore, this research was conducted to obtain information on morphology and germination process of the seed of candlenut. Direct measurement and observation of seed were quantified to observe the seed morphology. The germination process is also quantified through direct observation. The results of seed morphology showed that the candlenut had rough elliptical shell shape with about 6.08 cm in diameter and the shell thickness was approximately 2.56 cm. Germination process took 4-5 months with hypogeal germination type.